Kewenangan Peradilan Tata Usaha Negara dalam Mengadili Sengketa Keputusan Fiktif Negatif dan Fiktif Positif - Abdul Qodir Jaelani Jaelani (UIN Sunan Kalijaga Yogyakarta, 2017)
The results of the research indicate that, solving the problems through the StateAdministrative Court in the case of a request submitted to the State AdministrationOfficers / Officials in the context of providing public services can be passed through twoways, namely through negative and positive fictitious claims. The existence of both waysin the State Administrative Court is expected to be used as a mechanism for civilpersons or legal entities in claiming their rights to be served and as a means of control orsupervision for public service providers to work well in serving the community, because inthe end, the public is expected to be able to implement good governance in order toprovide legal certainty and justice for the community. The results of the research indicatethat, solving the problems through the State Administrative Court in the case of arequest submitted to the State Administration Officers / Officials in the context ofproviding public services can be passed through two ways, namely through negative andpositive fictitious claims. The existence of both ways in the State Administrative Courtis expected to be used as a mechanism for civil persons or legal entities in claiming theirrights to be served and as a means of control or supervision for public service providers towork well in serving the community, because in the end, the public is expected to be ableto implement good governance in order to provide legal certainty and justice for thecommunity.